2007
DOI: 10.2146/ajhp070072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a clinical pharmacist’s interventions on duration of antiretroviral-related errors in hospitalized patients

Abstract: The duration of prescribing errors was decreased when a clinical pharmacist monitoring patients receiving HAART intervened to resolve errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 21 publications
5
66
2
3
Order By: Relevance
“…Medication errors occur frequently in individuals with HIV/AIDS, often as a result of faulty communication at the interfaces of care, such as admission to and discharge from hospital. 145,146 Antiretroviral prescribing errors have been estimated to occur for between 5% and 30% of HIV-infected hospital inpatients, 8,147 with one prospective study reporting a prevalence as high as 72%.…”
Section: Prevention Of Errorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medication errors occur frequently in individuals with HIV/AIDS, often as a result of faulty communication at the interfaces of care, such as admission to and discharge from hospital. 145,146 Antiretroviral prescribing errors have been estimated to occur for between 5% and 30% of HIV-infected hospital inpatients, 8,147 with one prospective study reporting a prevalence as high as 72%.…”
Section: Prevention Of Errorsmentioning
confidence: 99%
“…145 Furthermore, when clinical pharmacists were actively involved in or leading the medication evaluation of HIV-positive patients being admitted to hospital, medication errors were prevented, error rates were further reduced, and the duration of uncorrected errors was significantly shorter. 8,149,157,158 Pharmacists can also be useful resources for residents and physicians, especially those with limited experience in HIV, who may be more prone to antiretroviral prescribing errors. 159,160 Pharmacists can provide advice regarding dosage adjustments to address drug interactions or organ insufficiencies, can suggest alternatives if current therapies or formulations are unsuitable or contraindicated, and can ensure that complete regimens are prescribed, including comedications, problems that a computerized physician order entry system is unlikely to be able to identify or help resolve.…”
Section: Medication Reconciliationmentioning
confidence: 99%
See 1 more Smart Citation
“…Se detectaron 296 PRM, de los cuales 132 correspondieron a PRM reales relacionados con la seguridad. Este valor es alto y puede ser causa de que la mayor cantidad de PRM en pacientes con infección por VIH, es atribuida a RAM e interacciones [3][4][5][6][7] . Sin embargo, no es posible comparar los datos entregados por este estudio con otras fuentes, ya que no existen reportes referentes a la incidencia de PRM en paciente seropositivos para VIH.…”
Section: Discussionunclassified
“…[18][19][20] The value of clinical pharmacists in the care of hospitalized patients with HIV reduces medication errors and medication costs. [21][22][23] In Kenya, nearly 7% of adults are infected with HIV and it continues to be one of the main causes for hospitalization in this setting. 15 Although data regarding the impact of clinical pharmacy services provided was not collected, a previous study in a different practice setting reported that students may reduce adverse drug events and medication costs.…”
Section: Discussionmentioning
confidence: 99%